STRATEGI HUMAS POLITEKNIK NEGERI JAKARTA DALAM PENERIMAAN MAHASISWA BARU - Ari Trisnawati; Maya May Syarah (Jurnal Komunikasi, 2017)
Public Relations is a management function that builds and maintains a good relationship between the organization and rewarding public that affect the success or failure of the organization. One strategy efforts to maintain good relations with external public who do Public Relations Jakarta State Polytechnic is to conduct socialization to some schools, which aims to find potential new students are qualified and competent through test selection  UMPN and PMDK-PN. In this case the authors use kulalitatif descriptive study that describes a situation in which the object being observed, conducted interviews author and observation to answer research questions. The research results show the success of Public Relations Jakarta State Polytechnic in improving the quality of new students through a few strategies that consist of doing an exhibition , socializing to each school , do a test track selection, and conducted annually. This activity received a positive response from all schools and prospective new students Jakarta State Polytechnic. Keywords: Public Relations Strategy, External Public, New Student Admission